Essays on contemporary issues in the South Korean economy - Saade, Ahmed J. (Cranfield University, 2023)
This doctoral thesis sheds light on some issues that are characteristic of the South Korean socioeconomic landscape today. In a series of three papers, I empirically address important questions faced by policy makers of this country, whilst also contributing to major debates currently taking place within the Economics discipline. In the first chapter, I investigate the effects of robotization on Korean workers’ labor supply from the lens of dynamic monopsony. I show that an increase in the density of industrial robots is associated with manufacturing workers becoming more responsive to a change in wages in their decision to quit to non-employment, and that the opposite is true for non-manufacturing workers. The second chapter contributes to the discussion on youth unemployment in South Korea, in tandem with the question of the high turnover rate within the nation’s Nursing profession. I find that the unemployment rate at time of graduation has scarring effects on Nurses’ wages, workhours, and subjective wellbeing. The final chapter of this dissertation tackles the problem of social isolation among Korean elders and contributes to the very small literature on the economic determinants of this phenomenon. I offer the first set of causal evidence linking the social isolation of elders with their adult children’s inheritance expectations.
Belghitar, Yacine - Associate Supervisor
Keywords: Socioeconomic; robotization; dynamic monopsony; non-employment; non-manufacturing; nursing